ON SOME WAYS OF CHILDREN’S FOREIGN LANGUAGE LEARNING (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article deals with the problems and importance of teaching foreign languages at an early age. It also includes information about the history of kindergarten, opinions of world scientists and psychologists in the field of education, and techniques that are commonly used in teaching foreign languages to children as well.